Perancangan Portal Berita Satelit TV Berbasis Website Menggunakan Metode Rapid Application Development dengan Framework Codeigniter - Widargo, Yulio Aldi; Saputra, Wahyu Andi (LPPM UNIKA Santo Thomas Medan, 2023)
Satelit TV is a local television station in Banyumas district. Initially, the products provided were not only television broadcasts, but also printed newspapers that presented local news. Over time, the production of the printed newspaper was stopped due to the diminishing interest from the public. However, Satelit TV does not yet have its own news portal site like most mass media. This certainly affects the competitiveness of local media. Because of the problems above, this study aims to design a Satelit TV news portal website. The method used to design this news portal website is Rapid Application Development (RAD). The focus of the RAD method is how to create or develop software in a relatively short time if the team's needs are well known. The results obtained are in the form of a web-based news portal that has passed the Black-box Testing method.